ORGANIZATIONAL AND LEGAL SUPPORT OF ANTI-CORRUPTION MECHANISMS OF PUBLIC ADMINISTRATION IN THE SPHERE OF CONSTRUCTION AND INFRASTRUCTURE RECOVERY - Leschynsky, Viktor (Public Management and Policy, 2026)
The relevance of the study stems from the fact that the sphere of construction and infrastructure recovery in Ukraine combines high capital intensity, a large volume of public investment, multi-level coordination, a complex project cycle, and heightened vulnerability to discretionary decisions, conflicts of interest, and manipulation at different stages of project implementation. Under the conditions of full-scale war and large-scale post-war reconstruction, anti-corruption support in this sphere acquires independent managerial significance. The purpose of the article is to substantiate the organizational and legal support of anti-corruption mechanisms of public administration in the sphere of construction and infrastructure recovery and to develop a risk-oriented model for their integration into the full management cycle of a recovery project. The methodological basis of the study combines systemic, institutional, comparative legal, logical-analytical, and content-analytical approaches. The source base includes Ukrainian legal acts, OECD analytical documents, studies by the National Agency on Corruption Prevention and the Basel Institute on Governance, materials from DREAM, CoST, Prozorro and DOZORRO, as well as recent academic works on corruption in construction projects, public procurement, and digital transparency. The article systematizes the stages of corruption risk concentration in the project cycle of construction and infrastructure recovery, characterizes the current institutional architecture of anti-corruption support, and generalizes the legal, institutional, digital, control, and civic instruments aimed at ensuring integrity. A cross-cutting model of anti-corruption support for a recovery project is proposed, combining prevention, digital traceability, internal and external control, audit, and public monitoring within a single integrity framework. It is shown that the practical value of this model lies in its potential use as an analytical and applied framework for improving the governance of recovery projects at the national and local levels. At the same time, the model requires further operationalization through a system of performance indicators, which opens a direction for further research.